2019
DOI: 10.4143/crt.2018.405
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profiles Associated with Chemoresistance in Patient-Derived Xenograft Models of Ovarian Cancer

Abstract: Purpose Recurrence and chemoresistance (CR) are the leading causes of death in patients with high-grade serous carcinoma (HGSC) of the ovary. The aim of this study was to identify genetic changes associated with CR mechanisms using a patient-derived xenograft (PDX) mouse model and genetic sequencing. Materials and Methods To generate a CR HGSC PDX tumor, mice bearing subcutaneously implanted HGSC PDX tumors were treated with paclitaxel and carboplatin. We compared gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…Of some pathophysiological relevance appear observations that overexpression of the non-catalytic p101 subunit of PI3Kγ led to oncogenic cellular transformation and malignancy, whereas the loss of p101 was reported to be sufficient to reduce in vivo tumor growth and metastasis to a similar extent to that of p110γ [51,204]. Of note upregulated p101 expression was associated with the progression of ovarian cancer chemoresistance in patient-derived xenograft murine models of ovarian cancer [205]. Interestingly, in contrast to the proposed tumor-promoting potential of p101 and p110γ, the Thr-607-phosphorylated p87 adapter may harbor tumor suppressor activity and attenuation of cell migration by forming a negative regulatory complex with p110γ to control PI3Kγ signaling [51,206].…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%
“…Of some pathophysiological relevance appear observations that overexpression of the non-catalytic p101 subunit of PI3Kγ led to oncogenic cellular transformation and malignancy, whereas the loss of p101 was reported to be sufficient to reduce in vivo tumor growth and metastasis to a similar extent to that of p110γ [51,204]. Of note upregulated p101 expression was associated with the progression of ovarian cancer chemoresistance in patient-derived xenograft murine models of ovarian cancer [205]. Interestingly, in contrast to the proposed tumor-promoting potential of p101 and p110γ, the Thr-607-phosphorylated p87 adapter may harbor tumor suppressor activity and attenuation of cell migration by forming a negative regulatory complex with p110γ to control PI3Kγ signaling [51,206].…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%
“…PIK3R5, as a member of PI3Ks, plays essential roles in cell growth, motility, and intracellular trafficking [ 13 , 14 ]. Abnormal expression of PIK3R5 exerts crucial roles in ovarian cancer [ 15 ]. Meanwhile, miRNAs, as a class of short non-coding RNAs, play diverse effects in cancers via modulating genes expression at post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Besides CD83 , a large number of the CD83 highly-associated genes (Person correlation >0.5, p < 0.01) within ovarian cancer transcriptome showed higher expression in ovarian cancer cells, especially in the EpCAM + /CD45 + subtypes ( Figure S1 ). CD83 highly-associated genes, such as ITGAM , IL1B , CYBB , PIK3R5 , BTK, and OSM , ectopically express in ovarian cancer cells or tissues, involving in ovarian cancer progression, hypoxia networks, and the development of chemoresistance [ 44 , 45 , 46 , 47 , 48 , 49 ]. Finally, we found that ovarian cancer patients’ survival inversely correlated with the level of CD83 expression in 907 ovarian cancer patients (low CD83 expression: 652, the high expression: 255), as patients with high CD83 expression lived significantly shorter compared with their counterparts with low CD83 expression ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%